IMPLEMENTATION OF ADOPTION IN SOUTH AFRICA: PERSPECTIVES FROM PRACTITIONERS IN THE WESTERN CAPE - Luyt, Jean; Swartz, Leslie (Social Work/Maatskaplike Werk, 2022)
In South Africa adoption as a form of alternative care had decreased despite a supportive legal and policy environment. This qualitative exploratory study explored adoption policy implementation. Semi-structured interviews were conducted with four social workers and two magistrates implementing adoption in the Western Cape. Data were thematically analysed using Lipsky’s theory of street-level bureaucracy. Results indicate significant problems in implementation, including lack of adoption services by the Department of Social Development (DSD) social workers; overuse of foster care; and difficulties in registration of the birth of abandoned babies and babies assumed to be foreign. Recommendations for practice are provided.